EVALUASI KEBIJAKAN PENATAAN PASAR TRADISIONAL, PUSAT PERBELANJAAN DAN TOKO MODERN DI KABUPATEN BLORA - Anshori, Wahyu Aji Wahid; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2017)
The Goverment of Blora Regency published regulation number 2 in 2012 about ordering of tradional market, shopping central, and modern store as one step to protect traditional market from many shopping center and modern market which built in Blora. The low level of performance that be background of this research. The research is aimed to evaluate ordering traditional market, shopping center, and modern store at Blora Regency. The implementer in this policy is Departement Of Trading, Cooperative and Micro Small Medium Enterpreneur. This research use evaluation indicator by William Dunn like effectiveness, sufficiency, responsiveness, and accuracy. The research method is qualitative and the technique data collect by interviews, observation, and documentation. The result, not maximum with the goals because there are shopping center and modern store are too close with traditional market, there is not yet partnership between shopping center and modern store with micro, small, and medium enterpreneur/tradional market and empowering that not comprehansive.